Feasibility study of utilization of palm oil mill effluent (POME) as a source for microalgae nutrients - Rifqi Ahmad Baihaqi; Wahyu Dizky Pratama (BIORE Scientia Academy, 2023)
As palm oil productivity increases, the waste produced will increase. Every palm oil industry produces liquid waste known as palm oil mill effluent (POME). POME contains very high BOD and COD so that it can inhibit microalgae growth. Therefore, comprehensive research is needed to find pre-treatment steps to reduce the COD and BOD content in POME before it is used as a medium for the growth and development of microalgae. The experimental mixture procedure carried out POME and microalgae according to the specified ratio. Research shows that Pond IV POME waste can be used as wild microalgae to grow, thereby reducing the BOD and COD levels of POME waste. Variable modifiers were applied to the volume of POME to the ratio of microalgae volume and the amount of nutrients provided. Microalgae growth with a ratio of 1:4 resulted in a decrease in BOD and COD to 61.66 ppm and 173.33 ppm from 110.6 ppm and 496.67 ppm. On the effect of providing C nutrition (120 ppm), resulted in lower BOD and COD at 65.33 ppm and 186.67 ppm, while the effect of providing N (40 ppm) nutrition resulted in lower BOD and reached 55.41 ppm and 158.33 ppm.